Pengaruh Parameter Sintering terhadap Stabilitas Fasa dan Struktur Mikro pada Komposit Titanium-Hidroksiapatit dengan Teknologi Serbuk: Review - Widyanita Harwijayanti; Tubagus Adytia Syarief Hidayat (CV. IRA PUBLISHING, 2026)
The increasing demand for orthopedic implants has driven the development of metals as biomedical materials. However, metals exhibit limited bioactivity, necessitating modifications to enhance their biological integration. One widely developed method is the fabrication of Titanium-Hydroxyapatite (Ti-HA) composites via powder metallurgy, utilizing hydroxyapatite for its similarity to human bone composition. This review analyzes 16 articles from Scopus and Google Scholar (2005-2023) based on material types, powder metallurgy parameters, and the physicochemical characterization of Ti-HA composites. The powder metallurgy process involves mixing, compaction, and sintering, during which the final properties are significantly influenced by the atmosphere, temperature, and holding time. A critical challenge is thermal stability, as hydroxyapatite decomposes above 800°C and titanium undergoes crystalline structural transformation beyond 882.5°C. During sintering, interparticle bonding and diffusion processes occur, triggering new phase formations and alterations in surface morphology. This process results in a final Ti-HA composite composition consisting of Titanium (Ti), Calcium (Ca), Phosphorus (P), and Oxygen (O). This study underscores the importance of precise control of temperature parameters to maintain material integrity during fabrication.